Standing and "survival" in the adult film industry - Jochen Lüdering (Philipps-University Marburg, School of Business and Economics, 2016)
It is said that knowing the right people is essential for one's career, which is supported in the literature on social capital. However, the empirical evidence in this field remains ambiguous, while the literature recognizes that "connections" certainly help finding any job at all, it remains unclear if there is a long-term benefit. While it is difficult to record a network structure in most industries, in the adult film industry collaboration between performers is easily observed. Consequently, a collaborative network can be constructed for which centrality measures can be calculated in order to estimate the effect on success. Unfortunately, success is not easily observed either. Hence, in this manuscript, the survival in the industry is used as a proxy for professional success. This assumption is justified by the economic argument that, in the absence of lock-in effects, performers will remain in the industry as long as it remains profitable. The profitability will not only depend on monetary aspects, but, in addition to economic costs, it takes potential costs from loss of reputation and personal well-being into account. The research at hand stands stands out by pioneering the use of centrality measures in duration models which, to the best of my knowledge, is a novel approach in the field. The results indicate that there is a strong correlation between network centrality and industry survival for the adult film industry.
Keywords: C41; D80; C55; 330; Duration Analysis; Professional Success; Network Analysis; Centrality; Social Capital